Morphological and molecular analyses reveal two new species of Guepinia from China - Shen, Yang; Fan, Li (Phytotaxa, 2020)
Guepinia alba sp. nov. and G. shanxiense sp. nov. are described and illustrated from Northern China in this paper. Morphologically, G. alba is distinguished from other Guepinia species by whitish basidiomata and 4-spored basidia while G. shanxiense is diagnosed by reddish orange basidiomata and ellipsoid to oblong ellipsoid basidiospores. Molecular phylogenetic analyses based on ITS and nrLSU sequences support the establishment of the two new species.